On general resampling algorithms and their performance in distribution estimation - Hall, Peter; Mammen, Enno (The annals of statistics, 1994)
Recent work of several authors has focussed on first-order properties (e.g., consistency) of general bootstrap algorithms, where the numbers of times that data values are resampled form an exchangeable sequence. In the present paper we develop second-order properties of such algorithms, in a very general setting. Performance is discussed in the context of distribution estimation, and formulae for higher-order moments and cumulants are developed. Arguing thus, necessary and sufficient conditions are given for general resampling algorithms to correctly capture second-order properties.
First available in Project Euclid: 11 April 2007
Gesehen am 28.02.2018